Effects of Biotic Factors on Population Fluctuations in Sympatric Field Murids - Kumar, Parmesh; Pashan, S C (Annals of Arid Zone, 2016)
The relative population density of various murids occurring in the agro-ecosystem of village Kakrod, Jind (Haryana) was estimated in Kharif and rabi crops. The structure divulged a combination of Millardia me/rada, Bandicota bcngalcnsis. Mus booduga, Rattus rattus and Mus musculus. A low population densityofmurids was recorded at the seedling stage of each crop which enhanced with the advancement of the crop growth reaching its peak at the maturiry stage. The innuence of various biotic factors on the wavering mechanisms of mllrids has been discussed.